2001
DOI: 10.4049/jimmunol.166.5.3107
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of a Costimulatory B7.2 (CD86) Protein on Human Salivary Gland Epithelial Cells that Interacts with the CD28 Receptor, but Has Reduced Binding to CTLA4

Abstract: B7 molecules expressed on classic APC play a critical role in the regulation of immune responses by providing activation or inhibitory signals to T cells, through the ligation with CD28 or CTLA4 receptors, respectively. We have recently described the expression of B7 molecules by the salivary gland epithelial cells (SGEC) of patients with Sjögren’s syndrome (also termed autoimmune epithelitis). The role of such expression needs to be clarified. Thus, in the present study, we sought to address the existence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 49 publications
6
81
0
1
Order By: Relevance
“…20 Later studies from the same research group proved constitutive expression of B7.2 molecules is sufficient to provide costimulatory signals to anti-CD3-stimulated T cells, implying a critical role for epithelial cells in the regulation of local immune responses in the salivary glands. 21,22 Evidence of the involvement of B7-H4 in the pathogenesis of various autoimmune disorders has been reported. 15 In our previous study, we found B7-H4 was not expressed on lymphocytes but on SGECs and the expression in pSS patients was lower than that in nonpSS controls, 16 adding the defect of B7-H4 expression on SGECs to the infiltration of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…20 Later studies from the same research group proved constitutive expression of B7.2 molecules is sufficient to provide costimulatory signals to anti-CD3-stimulated T cells, implying a critical role for epithelial cells in the regulation of local immune responses in the salivary glands. 21,22 Evidence of the involvement of B7-H4 in the pathogenesis of various autoimmune disorders has been reported. 15 In our previous study, we found B7-H4 was not expressed on lymphocytes but on SGECs and the expression in pSS patients was lower than that in nonpSS controls, 16 adding the defect of B7-H4 expression on SGECs to the infiltration of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, SGEC lines obtained from patients with Sjögren's syndrome have been shown to display a constitutively activated phenotype as suggested by the significantly increased spontaneous expression of several immunomodulatory molecules (including cytokines, chemokines, TLRs, and MHC, costimulatory, and adhesion molecules) compared with control SGEC lines from patients not found to have Sjögren's syndrome (17). Regarding B7-2 molecules, constitutive expression of the full-length B7-2 mRNA and protein is detectable in all SGEC lines (15). However, expression levels vary considerably among cell lines, ranging from low to high (albeit the latter are significantly lower compared with those of B cells, monocytes, and dendritic cells (DC)).…”
Section: Cell Linesmentioning
confidence: 99%
“…Previously, we have demonstrated that human non-neoplastic salivary gland epithelial cells (SGECs) 3 express functional fulllength and soluble protein forms of the B7-2 molecules (15). In this study, we describe the expression of a novel human B7-2 mRNA splicing variant by SGECs, as well as by peripheral blood monocytes.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The epithelial origin of cultured cells was routinely confirmed by staining with mAbs against epithelialspecific markers, including the various cytokeratins and epithelial membrane antigens and the absence of myoepithelial, fibroblastoid and lymphoid markers, using immunocytochemistry as previously described. 36,37 Evaluation of Furin, TACE and AREG Expression Cell Treatment SGEC were collected from culture media by centrifugation at 250 Â g and resuspended at 1 Â 10 6 cells/ml in McCoy's 5a modified medium. Cell suspensions (10 5 cells/well) were added to each well of a six-well plate (Thomas Scientific, Swedesboro, NJ, USA) and allowed to incubate for 24 h at 371C under 5% CO 2 .…”
Section: Microdissection and Primary Explant Culturementioning
confidence: 99%